Case report: Bilateral sudden deafness in acute middle cerebellar peduncle infarction: central or peripheral? - Yuan, Ziyun; Xiang, Lei; Liu, Ran; Yue, Wei (Frontiers in Medicine, 2023)
Background: The middle cerebellar peduncle (MCP) is the most common site associated with hearing impairment in acute ischaemic stroke. Narrowing or occlusion of the vertebrobasilar artery due to atherosclerosis is thought to be the main pathogenesis of MCP infarction. Most previous reports of MCP infarction have not been clear whether the patient's hearing impairment is localized to the center or periphery. Case presentation: We report a 44-year-old man with vertigo, tinnitus, and bilateral sudden sensorineural hearing loss (SSNHL) as the first symptoms. Pure-tone audiometry (PTA) revealed complete hearing loss in both ears. The brainstem auditory evoked potential (BAEP) and electrocochleography were normal. The otoacoustic emissions showed binaural cochlear dysfunctions. Acute bilateral MCP infarction was diagnosed by repeated brain magnetic resonance imaging. After antiplatelet, lipid-lowering, steroids and hyperbaric oxygen therapy, the PTA showed a clear improvement with 67 dB on the right and 73dB on the left at the 3-month follow-up.Conclusion: Vertebrobasilar diseases due to atherosclerosis should be routinely considered in middle-aged and elderly patients with vascular risk factors and bilateral hearing loss. Bilateral SSNHL can be a prodrome of acute MCP infarction and it can be peripheral. Brain MRI, brain MRA, BAEP, otoacoustic emissions, and PTA help to localize and qualify the diagnosis. Bilateral SSNHL localized to the periphery usually improves better and has a good prognosis. Early detection of hearing loss and intervention can help patients recover.